68‐3: Luminous Efficiency of SC‐OLED Improved by Distributed Bragg Reflector. Issue 1 (May 2016) - Wang, Chia-Sheng; Chen, Yi-Jiun; Lin, Hoang Yan
Abstract : A distributed Bragg reflector (DBR) structure was introduced to solar cell integrated‐organic light emitting device (SC‐OLED) to improve its luminous‐efficiency. Due to the reduction of unwanted absorption, the results show that the improvement in efficiency is about 43% for glass, and further improvement is upto 73% as higher index materials are used.